2013
DOI: 10.9758/cpn.2013.11.3.118
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation in Schizophrenia

Abstract: Transcranial direct current stimulation (tDCS) is an upcoming treatment modality for patients with schizophrenia. A series of recent observations have demonstrated improvement in clinical status of schizophrenia patients with tDCS. This review summarizes the research work that has examined the effects of tDCS in schizophrenia patients with respect to symptom amelioration, cognitive enhancement and neuroplasticity evaluation. tDCS is emerging as a safe, rapid and effective treatment for various aspects of schiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 52 publications
1
39
0
1
Order By: Relevance
“…Similarly, tDCS studies of AH in schizophrenia have been reviewed elsewhere (Agarwal et al, 2013;Brunoni et al, 2014), and typically employ an anodal-lDLPFC and cathodal-lTPJ montage. Findings are generally positive, such as that of Brunelin et al (2012) reviewed here, who reported a 31% reduction in AH severity after tDCS treatment, which was maintained at 3 months.…”
Section: Studies Related To Speech Language and Auditory Processingmentioning
confidence: 99%
“…Similarly, tDCS studies of AH in schizophrenia have been reviewed elsewhere (Agarwal et al, 2013;Brunoni et al, 2014), and typically employ an anodal-lDLPFC and cathodal-lTPJ montage. Findings are generally positive, such as that of Brunelin et al (2012) reviewed here, who reported a 31% reduction in AH severity after tDCS treatment, which was maintained at 3 months.…”
Section: Studies Related To Speech Language and Auditory Processingmentioning
confidence: 99%
“…For instance, in previous research, a 47% nonadherence rate to pharmacotherapy was found in patients suffering from schizophrenia [9]. As a result, in addition to pharmacotherapy, nonpharmacological interventions, such as transcranial magnetic stimulation (TMS) [10], transcranial direct current stimulation (tDCS) [11], and convulsive therapy [12], are increasingly being used in the treatment of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main reasons for the attractiveness of tDCS as a tool to modify neuroplasticity and neuronal activity [1] is that tDCS is a noninvasive brain stimulation technique that is well tolerated and easily employed with other peripheral therapies [2, 3]. Studies have highlighted tDCS as an alternative treatment method for schizophrenia [4], Alzheimer's [5], major depressive disorder [6, 7], stroke [8], and other neurological disorders. Moreover, tDCS has shown potential for aiding cognitive performance in healthy individuals with previous studies showing improvement of sustained attention [9], enhanced working memory [10], and enhanced functional connectivity in spatial navigation networks [11].…”
Section: Introductionmentioning
confidence: 99%